Intersex human rights. Issue 6 (2nd July 2020) - Bauer, Markus; Truffer, Daniela; Crocetti, Daniela
ABSTRACT: In this article we address the shift to naming intersex childhood medical treatment as serious human rights abuses (such as harmful cultural practices and/or and cruel, inhuman or degrading treatment). The article presents intersex rights claims, illustrates a brief history of intersex human rights strategies as witnessed by the co-authors, outlines specific human rights frameworks that have been applied to intersex rights claims by various UN committes, and discusses the implementation gap between human rights proclamations and national policies. Co-authors Bauer and Truffer present direct evidence from experience lobbying international human rights mecchnisms for intersex rights. Certain intersex movements began naming aspects of childhood intersex medical treatment as human rights abuses as early as the 1990s. Since the 2000s a body of human right's body proclamations on intersex has grown, from the CRC, CAT and CEDAW to the COE and the OHCHR. However, large implemantation gaps persists in most national regulation.